Application of 5 Finger Hypnosis Therapy and Murrotal Al-Qur'an to Reduce Anxiety in Patients Congestive Heart Failure (CHF) In Melati Room 2B RSUD Dr. Soekardjo, Tasikmalaya City - Peni Cahyati, Peni Cahyati; Ridwan Kustiawan, Ridwan Kustiawan; Iwan Somantri, Iwan Somantri; Syaukia Adini, Syaukia Adini; Novi Indriani, Novi Indriani (Jurnal Medika Cendikia, 2025)
CHF is a condition where the heart is unable to pump enough blood to supply nutrients and oxygen to the body's tissues. Heart failure patients will experience significant psychological impacts such as excessive anxiety, depression, sleep disorders, or excessive sensitivity, resulting in a decrease in quality of life. The aim of this scientific work is to provide an overview of the application of 5-finger hypnosis therapy and Murotal Al-Qur'an to CHF patients to reduce signs and symptoms of anxiety. The method used in this scientific paper is quantitative in the form of a case study approach that explores nursing problems, especially anxiety in patients with heart failure. The data collection techniques used were interviews, observation and physical examination as well as the HARS scale assessment which was used to determine the anxiety scores for the two subjects. The results obtained by both respondents experienced severe anxiety problems so they were given implementation in the form of 5 Finger hypnosis therapy and murrotal Al-Qur'an with a duration of 30 minutes for 3 days with an intensity of once a day. The conclusion is that both respondents experienced a decrease in anxiety after the intervention, but there was a difference in the decrease in anxiety scores between the two respondents. According to the HARS scale, the reduction in anxiety scores was better for respondent 1 because the severity of the disease suffered by the two respondents was different. Respondent 2 has a history of hypertension and diabetes mellitus since three years ago and is obese and has a decrease in intelligence in the form of memory loss, but in respondent 1 there is none. It is hoped that the problem of nursing anxiety in CHF patients will be given more attention because it not only impacts the physical condition but also disrupts the psychological condition, thus affecting the healing process.